ERK1/2-EGR1-SRSF10 Axis Mediated Alternative Splicing Plays a Critical Role in Head and Neck Cancer - Yadav, Sandhya; Pant, Deepak; Samaiya, Atul; Kalra, Neetu; Gupta, Sanjay; Shukla, Sanjeev (Frontiers in Cell and Developmental Biology, 2021)
Aberrant alternative splicing is recognized to promote cancer pathogenesis, but the underlying mechanism is yet to be clear. Here, in this study, we report the frequent upregulation of SRSF10 (serine and arginine-rich splicing factor 10), a member of an expanded family of SR splicing factors, in the head and neck cancer (HNC) patients sample in comparison to paired normal tissues. We observed that SRSF10 plays a crucial role in HNC tumorigenesis by affecting the pro-death, pro-survical splice variants of BCL2L1 (BCL2 Like 1: BCLx: Apoptosis Regulator) and the two splice variants of PKM (Pyruvate kinase M), PKM1 normal isoform to PKM2 cancer-specific isoform. SRSF10 is a unique splicing factor with a similar domain organization to that of SR proteins but functions differently as it acts as a sequence-specific splicing activator in its phosphorylated form. Although a body of research studied the role of SRSF10 in the splicing process, the regulatory mechanisms underlying SRSF10 upregulation in the tumor are not very clear. In this study, we aim to dissect the pathway that regulates the SRSF10 upregulation in HNC. Our results uncover the role of transcription factor EGR1 (Early Growth Response1) in elevating the SRSF10 expression; EGR1 binds to the promoter of SRSF10 and promotes TET1 binding leading to the CpG demethylation (hydroxymethylation) in the adjacent position of the EGR1 binding motif, which thereby instigate SRSF10 expression in HNC. Interestingly we also observed that the EGR1 level is in the sink with the ERK1/2 pathway, and therefore, inhibition of the ERK1/2 pathway leads to the decreased EGR1 and SRSF10 expression level. Together, this is the first report to the best of our knowledge where we characterize the ERK 1/2-EGR1-SRSF10 axis regulating the cancer-specific splicing, which plays a critical role in HNC and could be a therapeutic target for better management of HNC patients.